Subwavelength-scale off-axis optical nanomanipulation within Gaussian-beam traps - Zhou Lei-Ming; Sun Wan; Tao Zong-Qiang; Xiong Ning-Jun; Huang Chan; Jiang Xiao-Yun; Ren Yu-Xuan; Yang Yuanjie; Shi Yu-Zhi; Hu Ji-Gang; Zhan Qiwen (Nanophotonics)
It is generally recognized that there is only a single optical potential-well near the focus in optical traps with a focused Gaussian beam. In this work, we show that this classic Gaussian-beam optical trap has additional optical potential-wells for optical manipulation at the subwavelength scale in the off-focus transverse plane. The additional optical potential-wells are formed by the synergy of both the gradient trapping force and the transverse scattering force, though in previous studies the scattering force usually has adverse effect such as reducing trapping stability. These potential-wells work for not only the metallic particles, but also the high refractive-index dielectric particles. By engineering the contribution of the gradient force and scattering force through the particle size, the particle material and the position of the manipulation transverse plane, the force field and trapping potential-well can be tailored to trap/manipulate nanoparticles at different off-axis distance at the subwavelength scale. Our work provides new insight into optical tweezers and promises applications in optical nanomanipulation, nanoparticle sorting/separation, particle patterning and micro-fabrication on substrates.